Bromelain with peroxidase from pineapple are more potent to target leukemia growth inhibition - A comparison with only bromelain. (March 2019) - Debnath, Rahul; Chatterjee, Nabanita; Das, Subhadip; Mishra, Snehasis; Bose, Dipayan; Banerjee, Somenath; Das, Sujata; Saha, Krishna Das; Ghosh, Durgadas; Maiti, Debasish
Abstract: The natural anti-cancer agent bromelain is found to be beneficial for either single or multi-targeted therapy in gastric and skin carcinoma, by inhibiting cancer cell growth. Importantly, the presence of peroxidase enhances its biological efficiency. We have now evaluated a panel of cancer cell lines with bromelain in presence or absence of peroxidase to identify that the combination has higher apoptosis inducing potential in all those cell lines. Bromelain plus peroxidase (BM-PR) inhibited acute myeloid (K562) cell proliferation and altered the morphological features. Incidence of apoptosis was established by using annexin V exposure and this was confirmed that the cell cycle was arrested at G0/G1 phase in a concentration-dependent manner. BM-PR increased the intracellular ROS level and altered the mitochondrial membrane potential, as detected using dichlorofluores cin diacetate( DCFDA). It also regulated the expression of apoptosis-related proteins like Bax, Bcl2, caspase-3 and cytochrome besides causing up-regulation of p53 as determined by western blot analysis. These results suggest that BM-PR from pineapple induces apoptosis better than only bromelain in acute myeloid leukemia cells possibly via mitochondria dependent pathway. Highlights: Bromelain plus peroxidase (BP) from pineapple fruit induces better apoptosis in cancer cells than only bromelain (BM). In K562 cells BP induces apoptosis through mitochondrial dependent pathway. Fresh pineapple juice contains BP and may be used as a potent anticancer agent